LASER-PLASMA EUV RADIATION SOURCE : High brightness EUV sources based on laser plasma at using droplet liquid metal target. (1st June 2016) - Vinokhodov, A Yu; Krivokorytov, M S; Sidelnikov, Yu V; Krivtsun, V M; Medvedev, V V; Koshelev, K N
Abstract: We present the study of a source of extreme ultraviolet (EUV) radiation based on laser plasma generated due to the interaction of radiation from a nanosecond Nd : YAG laser with a liquidmetal droplet target consisting of a low-temperature eutectic indium–tin alloy. The generator of droplets is constructed using a commercial nozzle and operates on the principle of forced capillary jet decomposition. Long-term spatial stability of the centre-of-mass position of the droplet with the root-mean-square deviation of ∼0.5 μm is demonstrated. The use of a low-temperature working substance instead of pure tin increases the reliability and lifetime of the droplet generator. For the time- and space-averaged power density of laser radiation on the droplet target 4 × 10 11 W cm -2 and the diameter of radiating plasma ∼80 μm, the mean efficiency of conversion of laser energy into the energy of EUV radiation at 13.5 ± 0.135 nm equal to 2.3% (2π sr) -1 is achieved. Using the doublepulse method, we have modelled the repetitively pulsed regime of the source operation and demonstrated the possibility of its stable functioning with the repetition rate up to 8 kHz for the droplet generation repetition rate of more than 32 kHz, which will allow the source brightness to be as large as ∼0.96 kW (mm 2 sr) -1 .